A family of efficient estimators of the finite population mean in simple random sampling. Issue 5 (24th March 2018) - Pal, Surya K.; Singh, Housila P.; Kumar, Sunil; Chatterjee, Kiranmoy
ABSTRACT: In this paper an estimator of the finite population mean using auxiliary information in sample surveys has been proposed. The bias and mean squared error are obtained under large sample approximation. It has been shown that the proposed estimator performs better than some recently published estimators.